EVALUASI LAPANG TERHADAP DAMPAK APLIKASI INSEKTISIDA ISOPROCARB PADA SERANGGA PREDATOR DAN HAMA KUTU PERISAI AULACASPIS TEGALENSIS Zhnt. (HOMOPTERA: DIASPIDIDAE) DI PERTANAMAN TEBU - Rosma Hasibuan . (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2004)
Field evaluation of isoprocarb insecticide-application-effects on predacious insects and scale pest Aulacaspis tegalensis Zhnt. (Homoptera: Diaspididae) in sugarcane plantations. The sugarcane scale, Aulacaspis tegalensis Zehntner, is a new serious pest of sugarcane in Lampung Province. Over the years, most control practices against A. tegalensis rely on the use of chemical insecticide. A field study was conducted to assess the impact of isoprocarb (carbamate-insecticide) on sugarcane scale pests and their natural predators in sugarcane plantation. The results indicated that the application of isoprocarb (at recommended concentration = 1.25 mg/L) in sugarcane field failed to cause a significant reduction on scale pest populations. In contrast, the numbers of predacious insects was significantly reduced in isoprocarb-treated-field plots. The predacious insects in association with scale pests in sugarcane fields were predominantly coccinellids. Four species of primary predacious coccinellids attacking scale pests were: Chilocorus melanophthalmus, Chilocorus sp., Scymnus sp, and Telsimia sp. This field study indicated that the predacious species were more susceptible to isoprocarb than their prey.